"Convict Race": Racialization in the Era of Hyperincarceration - Seigel, Micol (Social justice, 2012)
Prison is the most powerful engine of racialization in the United States today. While radical imprisoned intellectuals have compelled large activist-scholar audiences, the ones who are not radicalized by their prison experiences are just as important to understand. This essay explores racial identification among people incarcerated at a medium-security facility in Indiana where the author teaches, noting both reactionary anti-racialism and expressions of commonality with African American history and struggle. The author brings together Foucault, Gramsci, Stuart Hall, theorists of anti-blackness, and abolitionist scholar-activists to analyze this complex white supremacist anti-racialism.